Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $m,n,p\in (0,+\infty)$ be constants and let $D$ be the region in the plane enclosed by lines $x=0,y=0$ and $x+y=1$. Calculate the following integral: $$\iint\limits_{D}x^{m-1}y^{n-1}(1-x-y)^{p-1}\mathrm{d}x\mathrm{d}y$$

Note: I know how to calculate it by the routine procedure, but the answer computed it in another way: It turned the simplex $D$ into the region $\Omega$ in $\mathbb{R}^3$ which is enclosed by planes $x=0, y=0, z=0$ and $x+y+z=1$, it then claimed that the original integral is equal to $$(p-1)\iiint\limits_{\Omega}x^{m-1}y^{n-1}z^{p-2}\mathrm{d}x\mathrm{d}y\mathrm{d}z $$

But I could not get why the triple integral is equivalent to the original double integral?(I know how to compute the triple integral, but I just can't see how it's equivalent to the double integral.)

share|cite|improve this question
up vote 2 down vote accepted

Let $\Omega = \{ (x,y,z) \;|\; (x,y) \in D \mbox{ and } 0 \leq z \leq 1-x-y \}$. Then turn the triple integral into a double $+$ a single integral...

$$(p-1)\iiint\limits_{\Omega} x^{m-1}y^{n-1}z^{p-2} \,dV = \iint\limits_D \left(\int_0^{1-x-y} (p-1)x^{m-1}y^{n-1}z^{p-2}\,dz\right)\,dA$$ $$= \iint_D \left. x^{m-1}y^{n-1}z^{p-1} \right|_0^{1-x-y}\,dA = \iint_D x^{m-1}y^{n-1}(1-x-y)^{p-1}\,dA$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.